Inhibition of Horseradish Peroxidase Activity by Boroxine Derivative, Dipotassium-trioxohydroxytetrafluorotriborate K2[B3O3F4OH] - Jelena Ostojic; Safija Herenda; Semira Galijasevic; Borivoj Galic; Mladen Milos (Journal of Chemistry)
Recently research shows that horseradish peroxidase, HRP, when combined with other compounds, is highly reactive toward different human tumour cells and that better understanding of catalytic mechanism and inhibition HPR could lead to a new targeted cancer therapy. Thus, the inhibition of HRP activity by dipotassium-trioxohydroxytetrafluorotriborate K2[B3O3F4OH] was investigated for possible explanation of previously observed antitumour activities of this promising drug. HRP activity was studied under steady-state kinetic conditions by a spectrophotometric method. In the absence of the inhibitor values of Km = 0.47 mM and Vmax = 0.34 mM min−1, respectively, were determined. The hydrogen peroxide H2O2 kinetic measurements show a competitive inhibition with the inhibition constant KI = 2.56 mM. The activation energy Ea values were found to be very similar for both reactions; in the absence of inhibitor activation energy was 17.7 kJ mol−1 and in the presence of inhibitor activation energy was 16.3 kJ mol−1. The values of Arrhenius constants were found to be different; A = 4.635 s−1 was measured in the absence of inhibitor while in the presence of inhibitor Arrhenius constant was 1.745 s−1 showing that K2[B3O3F4OH] initiates conformational change in the structure of the HRP and subsequently reduces its activity.